2008
DOI: 10.1016/j.molstruc.2008.05.047
|View full text |Cite
|
Sign up to set email alerts
|

DFT and time-resolved IR investigation of electron transfer between photogenerated 17- and 19-electron organometallic radicals

Abstract: The photochemical disproportionation mechanism of [CpW(CO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…With the assignment of radicals R 1 through R 4 presented in the preceding section, we can build a complete picture of the ligand substitution dynamics, as depicted in Figure 5 is surprising but comparable to earlier results reported for tungsten radicals [21][22][23][24]. The observation of similar reactivity for the two different metals is a strong indication of the generality of the reaction mechanism.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…With the assignment of radicals R 1 through R 4 presented in the preceding section, we can build a complete picture of the ligand substitution dynamics, as depicted in Figure 5 is surprising but comparable to earlier results reported for tungsten radicals [21][22][23][24]. The observation of similar reactivity for the two different metals is a strong indication of the generality of the reaction mechanism.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, we assign R 3 (1910 cm -1 ) to the 17e radical CpFe(CO)P(OMe) 3 and R 4 (1899 cm [167]. We have reported that steric effects play a major role in determining the dynamics of 19e radicals for the analogous tungsten system (see Chapter 3) [21,23]. We thus expect that a 19e radical with two Lewis bases is less likely to form in the presence of a larger Lewis bases.…”
Section: Identification and Molecular Structures Of Radical Intermedimentioning
confidence: 96%
See 3 more Smart Citations